Detecting Fish Diversity in Urban‐Impacted Ecosystems: A Comparative Approach of eDNA Metabarcoding and UVC - Arthur Chung; Y. C. Kam; Stanley K. H. Shea; Celia Schunter (Environmental DNA)
ABSTRACT Comprehensive assessments of coastal biodiversity in complex coral communities are crucial but challenging, particularly under unfavorable conditions such as poor underwater visibility in urbanized and eutrophic environments. Here we aim to examine the scope of underwater diversity detection and community shifts across habitat transitions spanning different geographic regions in Hong Kong SAR, a highly urbanized coastal city with limited underwater visibility of 3.93 ± 1.25 m during the sampling period. We employ and compare two methods: 12S rRNA eDNA metabarcoding coupled with custom built reference database and simultaneous extensive underwater visual census (UVC) surveys. eDNA detected a higher species richness per site. Yet, each survey method featured a distinct species profile with associated trophic guilds, where 98 (32.3%) species found exclusively by UVC and 120 (39.6%) species detected only by eDNA. eDNA featured species from diverse habitats and evolutionary distances, including cryptic and large mobile fishes, offering enhanced prediction on local ecosystem functions. eDNA also recorded 90 putative species that had never been recorded in additional seven yearlong UVC dataset, with seven prospective new occurrence records to the territorial waters. UVC on the other hand was more efficient in documenting reef‐associated species. Both methods captured similar patterns of community spatial structure along the habitat transitions while only eDNA detected more large fish species in offshore compared to sheltered inshore environments, This may suggest inshore overfishing and incapability of UVC in surveying large mobile species in turbid environments. Considering the discrepancies between two methods, we highlight the importance of complementing both UVC and eDNA metabarcoding survey for a complete overview of local biodiversity under unfavored underwater conditions in an urbanized seascape.